Evaluation of the complementarity between wind and solar resources and considerations stability in the electricity sector - de Souza Muniz, Ewerton; Salustiano da Silva Junior, Rosiberto; Alves da Silva, Taiane; Do Nascimento Vasconcelos, Luana; Fernando de Fonseca Lyra, Roberto; Antonio Lima Moura, Marcos [UNESP]; Santos de Oliveira Silva, Luan (Revista Brasileira de Geografia Fisica, 2025)
The study aims to evaluate the performance of a photovoltaic system installed in Alagoas, Brazil, through the analysis of the Performance Ratio (PR) and its relationship with meteorological variables. Data was collected from a micro photovoltaic power plant, including energy generation, nominal power, and meteorological data (solar irradiation, temperature, relative humidity, wind speed and precipitation). The PR was calculated to assess the actual efficiency of the system compared to its nominal capacity. The system used a photovoltaic arrangement with microinverters, which, according to literature, achieve the best PR results. Analysis was performed on several meteorological variables such as solar irradiation, relative humidity, air temperature, rainfall, and wind speed. Additionally, soiling was considered to observe its impact on the performance of the array. The installation achieved excellent results, with an average PR value of 89.70%. Data from the Automatic Weather Station (AWS) and the photovoltaic array were also used to develop a photovoltaic equation, enabling the creation of a photovoltaic map for the studied region and areas with similar climatic conditions.
Avaliação da eficiência da produção de energia solar, para um sistema fotovoltaico residencial
Keywords: meteorological variables; Performance Ratio; photovoltaic equation